2004
DOI: 10.1002/gps.1197
|View full text |Cite
|
Sign up to set email alerts
|

Use of constraints and their correlates in Norwegian nursing homes

Abstract: Constraint is frequently used in nursing homes, and most frequent toward patients with severe dementia, aggressive behaviour or low ADL function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 39 publications
1
64
1
4
Order By: Relevance
“…Of the patients with dementia in Norwegian nursing homes, 71% have at least one clinically significant neuropsychiatric symptom as measured by the Neuropsychiatric Inventory . Neuropsychiatric symptoms cause distress for the patients, their relatives and nursing home staff (Sourial et al, 2001), and increase the incidence of physical restraints in the nursing homes (Werner et al, 1989;Kirkevold et al, 2004) and the prescription of psychotropic drugs (Bartels et al, 2003). As dementia becomes more severe, the NPS occur more frequently .…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients with dementia in Norwegian nursing homes, 71% have at least one clinically significant neuropsychiatric symptom as measured by the Neuropsychiatric Inventory . Neuropsychiatric symptoms cause distress for the patients, their relatives and nursing home staff (Sourial et al, 2001), and increase the incidence of physical restraints in the nursing homes (Werner et al, 1989;Kirkevold et al, 2004) and the prescription of psychotropic drugs (Bartels et al, 2003). As dementia becomes more severe, the NPS occur more frequently .…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, their autonomy was overruled, despite the fact that there was no danger to life or health. As previous studies have shown, 4,7,12,15,16,19,28 RNs using coercive measures had convinced themselves that residents' problematic behaviour was due to lack of insight, and therefore, constraints were seen as appropriate. It seems as though legal rights were understood as actions to prevent falls or harm, and not as actions to support autonomy and non-coercive dementia care.…”
Section: Discussionmentioning
confidence: 97%
“…In one study, staff level did not reduce the use of coercive treatment, 4 and in another, understaffing was a significant factor in promoting such treatment. 16 In the theme 'nursing strategy with coercive treatment under specific circumstances', the RNs prioritized the residents' autonomy, but not non-coercive nursing care.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The mean staffing ratio is 0.30 for RUs and 0.35 for SCUs. The proportion of unskilled staff is 11.9% in RUs and 12.6% in SCUs [28]. …”
Section: Methodsmentioning
confidence: 99%